ANALISIS KEBERHASILAN SISTEM INFORMASI APLIKASI SHOPEE - Akhmad Afnan; Yuni Putri Yustisi (JURNAL CAFETARIA, 2023)
The Shopee application as one of the developers of the E-Commerce platform is one of the largest developers in Indonesia. Based on SimilarWeb data, Shopee's visit rate during August 2021 recorded a total of 26.92 million unique daily actives users (DAU) accessing it via Android mobile devices. At the end of the 2021 quarter, Shopee's active users reached 130 million people. The focus of this research is on the success factors of the Shopee application and its impact on improving customer service. The research model that forms the basis of the research is the Information Systems Success Model developed by Delone Mclean. The developed model can be used to predict satisfaction, use and net benefits of the Shopee application, although there are several constructs that are not supported.